Analisis SWOT Dalam Pengembangan Koperasi pada Koperasi Unit Desa (KUD) Rukun Tani Cilongok - Mukarromah, Laili; Maulida, Indah Ilma; Maula, Muhammad Ihza; Sulasih, Sulasih (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
Abstract. This study aims to analyze the internal and external conditions of the Village Unit Cooperative (KUD) Rukun Tani Cilongok using a SWOT analysis approach to formulate appropriate development strategies to improve the performance and competitiveness of the cooperative in Banyumas Regency. The background of this study is the strategic role of cooperatives, especially KUD, as pillars of rural economy in Indonesia facing various performance problems and competitive challenges. The research method employs a qualitative approach with data collected through in-depth interviews with KUD management and literature review. The analysis identifies KUD's strengths such as strategic location, diversified business units, and price competitiveness; weaknesses including limited competent human resources and capital fluctuations; opportunities from agricultural market potential and government programs; and threats from competition and market liberalization. Based on the SWOT analysis, recommended development strategies include internal strengthening through human resource development, membership inclusion, and utilization of agricultural market opportunities with product and service innovation. These strategies are expected to enhance KUD's performance and competitiveness in supporting the village economy.